2023
DOI: 10.1097/ccm.0000000000005915
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Power Delivered by Noninvasive Ventilation Contributes to Physio-Anatomical and Clinical Responses to Early Versus Late Proning in COVID-19 Pneumonia*

Giovanni Musso,
Claudio Taliano,
Elena Paschetta
et al.

Abstract: OBJECTIVES: To study: 1) the effect of prone position (PP) on noninvasive ventilation (NIV)-delivered mechanical power (MP) and 2) the impact of MP on physio-anatomical and clinical responses to early versus late PP in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia. DESIGN: Nonrandomized trial with inverse probability of treatment weighted-matched groups. SETTING: HUMANITAS Gradenigo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Small case series (2, 3), larger observational studies (4–6), clinical trials (7, 8), and meta-analyses (9, 10) of awake-prone positioning for COVID-19 pneumonia have now consistently reported improved oxygenation with many studies finding reductions in endotracheal intubation, although not all trials have found benefit (11–13). In today’s issue of Critical Care Medicine , Musso et al (14) seek to expand this literature base by addressing, in addition to efficacy, the timing of awake-prone positioning and potential physiologic mechanisms for the observed benefit.…”
mentioning
confidence: 99%
“…Small case series (2, 3), larger observational studies (4–6), clinical trials (7, 8), and meta-analyses (9, 10) of awake-prone positioning for COVID-19 pneumonia have now consistently reported improved oxygenation with many studies finding reductions in endotracheal intubation, although not all trials have found benefit (11–13). In today’s issue of Critical Care Medicine , Musso et al (14) seek to expand this literature base by addressing, in addition to efficacy, the timing of awake-prone positioning and potential physiologic mechanisms for the observed benefit.…”
mentioning
confidence: 99%